O estudante gaúcho, a ciência e a tecnologia: uma análise dos interesses estudantis por meio do instrumento ROSES - RS - Rosa, Poliana Antunes da (2023)
If on the one hand science and technology are increasingly present in contemporary society, on the other hand, the demotivation of students for the teaching of Natural Sciences and for pursuing scientific careers have been the object of study in various academic research. The investigation of how young people relate to scientific and technological knowledge is essential for the educational field, especially at a time when High Schools are undergoing structural reformulations and there are many uncertainties regarding the methodology and application of the proposed New High School and its formative itineraries. In this sense, this research is based on the instrument ROSE-The Relevance of Science Education, aimed at young people aged 15 years, already validated and implemented in more than 40 countries. This questionnaire was designed to investigate students' interests, opinions and attitudes towards Science and Technology. This study discusses the Rio Grande do Sul version of the instrument, entitled ROSES-RS 2022, in which, in a representative state sample, the objective was to know the Science and Technology themes that are of interest to high school students in Rio Grande do Sul, associating them with the Thematic Units of the Natural Sciences Knowledge Area and its Technologies of the National Common Curriculum Base (BNCC). The research, of a quantitative and qualitative nature, analyzed data from 54 state schools in the nine Functional Planning Regions of the State (RFs), covering 1892 students. The investigation revealed that the items with the highest averages among young people from Rio Grande do Sul are: "How to provide first aid" and "Possibility of life outside Earth", while "Detergents and soaps and how they work" was the item with the lowest average of interest. It is noteworthy that the item that reached the highest average among students is not present in the Thematic Units of Natural Sciences and their Technologies. In addition, the Thematic Unit Life and Evolution stands out when we verify student interests according to the Thematic Units of the area. In 55.6% of the FRs, the items “How to provide first aid” and “Possibility of life outside Earth" prevailed as the first student preferences, while in 77.8% of the FRs, the “Detergents and Soaps and How They Work” and “Fungus Around Us” were the least interesting items for young people. The Technical and Professional Training itinerary was the one that stood out, with 48% of the nominations, followed by Natural Sciences and its Technologies with 30% of the student choices. Since we have before us a scenario of important challenges, the scientific and technological interests of the young people from Rio Grande do Sul revealed in this research, present elements capable of helping to meet the demands that come from education and public policies aimed at High School, mainly those linked to the area of Natural Sciences and its technologies and proposes relevant considerations on actions that talk to teachers, curriculum and regional educational policies.